Answer:
x=5
Step-by-step explanation:
Simplifying 5x + -7 = 2x + 8 Reorder the terms: -7 + 5x = 2x + 8 Reorder the terms: -7 + 5x = 8 + 2x Solving -7 + 5x = 8 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -7 + 5x + -2x = 8 + 2x + -2x Combine like terms: 5x + -2x = 3x -7 + 3x = 8 + 2x + -2x Combine like terms: 2x + -2x = 0 -7 + 3x = 8 + 0 -7 + 3x = 8 Add '7' to each side of the equation. -7 + 7 + 3x = 8 + 7 Combine like terms: -7 + 7 = 0 0 + 3x = 8 + 7 3x = 8 + 7 Combine like terms: 8 + 7 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
Answer:
f(g) = -3( x^2 -x-6) -6 = -3x^2+3x+12
Answer:
-2×h
Step-by-step explanation:
because it drops-2 by hour so multiply-2 by the difference of hours
Answer:
You add a bar till the 2 for the 9-10. You add bars till 6 for the 11- 12. You add bars till 8 for the 13-14. You add bars till the 4 for the 15-16.
Step-by-step explanation: